Donor-acceptor based solvent-free organic liquid hybrids with exciplex emission and room temperature phosphorescence - Wakchaure, Vivek Chandrakant; Veer, Sairam D.; Nidhankar, Aakash D.; Goudappagouda; Nayak, Rashmi; Asokan, Kiran; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Chemical Communications, 2022)
Solvent-free organic liquids are well-known for their excellent luminescence features. Hence, the recent developments in this area have marked them as potential emitters with high quantum yield and enhanced processability. The support of an available liquid matrix enables doping to deliver hybrid liquids with intriguing luminescence features. In this direction, we report solvent-free liquid donor-acceptor pairs with exciplex emission and room temperature phosphorescence at very low acceptor loading. The underlying weak intermolecular interactions have been revealed by 2D NMR techniques and theoretical calculations. The formation of large-area thin films by exciplex and phosphorescent liquid hybrids will encourage the development of scalable lighting and display materials.